Memorization of the Qur’an: A study of early Muslim pedagogy - Bensaid, Benaouda; Machouche, Salah (2013)
The research seeks to investigates variety of aspects of early Muslims education, with special reference to method of memorization of the Quran. The research discusses two major currents led by two prominently scholarly figures in the Fourteen Century, al-Qabisi and Ibn Khaldun. Through comparison of their arguments, the research concludes that approach of memorizing the Quran as set according to early Islamic pedagogy is holistic and embraces diverse external components to the learning process and cognitive factors such as the social and spiritual development as well as the wellness of students. These considerations emanate from the belief that the Qur’an memorizers caries blessing within themselves, collects large divine reward and that their rational and emotional states are positive. The research sought to explore the effects of technical style and to assess Quran memorization within the broader perspective of madrassa system which includes development of many learning skills and capabilities. The research on the approach to and style of memorization is instrumental not only to current reform of Islamic learning curriculum but also useful to understanding of issue of creativity, and to issues of comprehension versus textual known in our madrasah systems of education.